The Maintenance of Kualuh Malay Language of Labuhanbatu Utara Students in Medan - Husna, Nidaul; Pulungan, Anni Holila; Br.Pane, Isli Iriani Indiah (Jurnal Bahasa dan Sastra, 2024)
Language preservation is an important effort to maintain the continuity of language and culture. This study aims to: (1) identify the factors that influence the use of Kualuh Malay among students from Labuhanbatu Utara, (2) analyze the strategies used by students to maintain the language, and (3) evaluate the motivation behind the language maintenance. A descriptive-qualitative method was chosen to gain in-depth understanding through observation, interviews, and documentation. The participants of this study consisted of 18 students. The results show that there are seven factors that influence Kualuh Malay language, including visits to hometowns and usage in the family. Students apply strategies such as family language policy and use in cultural activities. The main reason Labura students maintain Kualuh Malay is their pride of identity. This research recommends that the people of Labuhanbatu Utara continue to integrate the use of Kualuh Malay in daily life and support its preservation in education.